Two new mite species of the genus Geckobia Mégnin (Acariformes: Pterygosomatidae) from Israel - Fajfer, Monika (Zootaxa, 2023)
Two new species of pterygosomatid mites parasitizing Sinai fan-fingered gecko Ptyodactylus guttatus Heyden (Phyllodactylidae) from Israel are described: Geckobia bochkovi sp. nov. and Geckobia synthesys sp. nov. The former species is the most similar to Geckobia squameum Bertrand, Paperna, and Finkelman, 1999, but differs by the presence of a well-outlined, slightly concave propodonotal shield in its anterior and posterior margin, fine-pointed dorsal setae that slightly increase in length from the anterior to the posterior part of the idiosoma, leg setae l’FI and l’GI, shape of coxal setae 4a, 4b and 4c which are slender and smooth or with barely discernible serration. The latter species is most similar to Geckobia keegani Lawrence, 1953 but differs in the shape of the propodonotal shield, which is almost straight in its posterior margin, the presence of five pairs of setae on the shield, 19–28 pairs of idiosomal ventral setae, three genital setae and leg setae l’GI, l’GIV, vFI–II, vFIII–IV, lFIII–IV and vTrIV.